Enforcing Workplace Pension Rights for Unionized Employees: Is There a Weber Gap Workplace Pensions: Next Generation or Final Frontier - Shilton, Elizabeth (Canadian Labour and Employment Law Journal, 2015)
In the Weber case, the Supreme Court of Canada enlarged the scope of jurisdiction of labour arbitrators by holding that they have exclusive jurisdiction over all disputes arising not only expressly, but also "inferentially," from a collective agreement. Unfortunately, the expanded jurisdiction conferred on arbitrators was not accompanied by any direction as to where they should look for the normative standards necessary to adjudicate claims where those stan- dards are not provided by the collective agreement, creating the potential for what scholar and arbitrator Brian Etherington has called a Weber gap. There is the potential for such a Weber gap in relation to workplace pension issues, which have traditionally been dealt with by the courts. In Bisaillon v. Concordia University, the Supreme Court of Canada applied a liberal version of the Weber test to a pension dispute, holding that it belonged within the exclusive jurisdic- tion of an arbitrator. Courts and arbitrators have had starkly different responses to this decision: courts have embraced the Court's liberal approach and refused jurisdiction over many pension claims they would previously have dealt with, while arbitrators have taken a narrower view and have been hesitant to expand their own jurisdiction. This divergence has led in practice to an enforcement gap that may leave some unionized employees without access to an effective forum in which to vindicate pension rights. The author proposes that this problem could be addressed through a liberalization of arbitral practice, through collective bargaining, or through legislative reform.